A Retrospective Analysis of Early Complications in Endoscopic Third Ventriculostomy for Obstructive Hydrocephalus - Atta Ur Rehman, Sarwat Rasheed, Muhammad Haroon Bilal (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Endoscopic third ventriculostomy (ETV) is a well-established procedure for treating obstructive hydrocephalus. While it is considered an effective alternative to ventriculoperitoneal shunts, early postoperative complications continue to pose challenges in clinical practice. This study aimed to evaluate the patterns and rates of early complications in a cohort of 96 patients undergoing ETV. Objective: To determine the frequency and types of early complications associated with ETV in 96 patients diagnosed with obstructive hydrocephalus. Methods: A retrospective study was conducted on 96 patients who underwent ETV at Neurosurgery, DG Khan Medical College, DG Khan from March 2020 to October 2021. Data were collected on patient demographics, etiology, surgical outcomes, and early complications. A regression analysis was performed to identify factors influencing complication rates. Results: The cohort included 60 males (62.5%) and 36 females (37.5%), with a mean age of 32.4 years (range: 2–70). The most common cause of hydrocephalus was aqueductal stenosis (45%), followed by tumor-related hydrocephalus (30%) and post-infectious hydrocephalus (25%). Early complications included cerebrospinal fluid (CSF) leakage (4.2%), wound infection (2.1%), meningitis (1.0%), minor bleeding (2.1%), seizures (3.1%), and one case of in-hospital mortality (1.0%). Conclusion: ETV is a safe procedure for the treatment of obstructive hydrocephalus with a low incidence of early complications. Postoperative monitoring remains critical for timely management of potential adverse events. Keywords: Endoscopic third ventriculostomy, obstructive hydrocephalus, early complications, cerebrospinal fluid leakage, wound infection, seizures, mortality.